Improvement the Soil Subgrade using Sisal Fiber and Bagasse Ash (International Journal of Innovative Research in Computer Science & Technology, 2022)
The effects of addition of Bagasse ash and  Sisal Fibers in soil on MDD and OMC relationship different  percentages of bagasse ash is added and optimized. Then this optimized bagasse ash soil is the mixed with the different  lengths and different percentages of Sisal Fibers. It is interpreted that there is increase in OMC  and decrease in MDD with addition of Bagasse Ash. But the  values of CBR and UCS are increased with 4% of BA and  Sisal Fiber length 4cm at 1.5%. There is increase in the  percentage of UCS, when sample were prepared with 2%,  4% by 3.02%, 4.70% and decrease in percentage of UCS,.  The experiments in combined sample of BA and Sisal Fiber  (2cm, 4cm, 6cm)shows that the maximum value of UCS are  obtained at 4cm length with 1.5% by weight, which is found  to be 3.73 kg/cm2. The percentage increase as compared to  the raw soil is 25.16%. The soaked CBR value of the raw soil  with 4% BA is 2.59%. The soaked CBR value of combined soil sample with 4% BA, 1.5% of Sisal Fiber of  4cm length is found to be 3.09%, the increase in CBR value  as compared to raw soil is 70.16%.
Keywords: Bagasse Ash; Sisal Fiber; OMC; CBR; MDD; UCS